Angular momentum evolution of cool stars: Toward a synthesis of observations and theory before and after the ZAMS. Issue 1 (6th February 2013) - Meibom, S.; Barnes, S.A.; Covey, K.; Jeffries, R.D.; Matt, S.; Morin, J.; Palacios, A.; Reiners, A.; Sicilia‐Aguilar, A.; Irwin, J.
Abstract The coexistence of fast and slowly rotating cool stars in ZAMS clusters – forming distinct sequences in the color vs. rotation period plane – is providing clues to differences in their pre main‐sequence angular momentum evolution. This Cool Stars 17 splinter was dedicated to a discussion of new observational and theoretical results that may help discriminate between proposed mechanisms for early angular momentum regulation and help us explain the observed ZAMS dichotomy